Affinity purification of O-acetylserine(thiol)lyase from Chlorella sorokiniana by recombinant proteins from Arabidopsis thaliana - Salbitani, Giovanna; Wirtz, Markus; Hell, Rüdiger (Metabolites, 2014)
In the unicellular green alga Chlorella sorokiniana (211/8 k), the protein O-acetylserine(thiol)lyase (OASTL), representing the key-enzyme in the biosynthetic cysteine pathway, was isolated and purified to apparent homogeneity. The purification was carried out in cells grown in the presence of all nutrients or in sulphate (S) deprived cells. After 24 h of S-starvation, a 17-fold increase in the specific activity of OASTL was measured. In order to enable the identification of OASTL proteins from non-model organisms such as C. sorokiniana, the recombinant his-tagged SAT5 protein from Arabidopsis thaliana was immobilized by metal chelate chromatography. OASTL proteins from C. sorokiniana were affinity purified in one step and activities were enhanced 29- and 41-fold, from S-sufficient and S-starved (24 h) cells, respectively. The successful application of SAT/OASTL interaction for purification confirms for the first time the existence of the cysteine synthase complexes in microalgae. The purified proteins have apparent molecular masses between 32-34 kDa and are thus slightly larger compared to those found in Arabidopsis thaliana and other vascular plants. The enhanced OASTL activity in S-starved cells can be attributed to increased amounts of plastidic and the emergence of cytosolic OASTL isoforms. The results provide proof-of-concept for the biochemical analysis of the cysteine synthase complex in diverse microalgal species.